Study of the Behavior of Fish Caught with Sero Through Echofishfinder Observation in the Waters of the Tallo River Makassar - Ibnu Malkan Hasbi; Jumrawati Jumrawati; Husni Angraeni (Agrikan: Jurnal Agribisnis Perikanan, 2020)
The study of fish behavior with echofishfinder observations was carried out to determine the composition of the catch, economic size of the catch and oceanographic parameters of the behavior of fish caught through echofishfiner observations in the Tallo river. This research was carried out in July-October 2020 at five fishing gear points. sero. The research method used is an experimental method which aims to investigate the possibility of a causal relationship by controlling and controlling. Data collection is obtained from the catch of sero fishing gear from fishermen then the catch is separated based on 3 types of catch, namely main, secondary and waste. Research results show that. The data analysis used in this study is the composition of the economic catch and the Tss test for oceanographic parameters. The results showed that the movement of fish was dominated by small fish groups that came schooling and alone (Solitary). The main types of catch are baronang fish (Siagnus Sp), bycatch, namely tembang fish (sardinella), and puffer fish (Diodotinidae). The measured oceanographic parameters were temperature, current velocity, and chlorophyll-a from several parameters that were closest to the total main catch, namely the chlorophyll a parameter.